B7-H3 CAR-T cell therapy combined with irradiation is effective in targeting bulk and radiation-resistant chordoma cancer cells - Kun Wang; Gianpietro Dotti; Soldano Ferrone; Yufeng Wang; Yin P Hung; Tao Ma; Giulia Cattaneo; Xinhui Wang; David O Osei-Hwedieh; Tara A Walhart; Joseph H Schwab (Journal for ImmunoTherapy of Cancer)
Background Chordoma is a slow-growing, primary malignant bone tumor that arises from notochordal tissue in the midline of the axial skeleton. Surgical excision with negative margins is the mainstay of treatment, but high local recurrence rates are reported even with negative margins. High-dose radiation therapy (RT), such as with proton or carbon ions, has been used as an alternative to surgery, but late local failure remains a problem. B7-H3 is an immune checkpoint, transmembrane protein that is dysregulated in many cancers, including chordoma. This study explores the efficacy of B7-H3 chimeric antigen receptor T (CAR-T) therapy in vitro and in vivo.Methods Chordoma cancer stem cells (CCSCs) were identified using flow cytometry, sphere formation, and western blot analysis. The expression of B7-H3 in paraffin-embedded chordoma tissue was determined by immunohistochemical staining, and the expression of B7-H3 in chordoma cells was measured by flow cytometry. Retroviral particles containing either B7-H3 or CD19 CAR-expressing virus were transduced into T cells derived from peripheral blood mononuclear cells isolated from healthy human donor blood to prepare CAR-T cells. Animal bioluminescent imaging was used to evaluate the killing effect of CAR-T cells on chordoma cells in vivo. An irradiator was used for all irradiation (IR) experiments.Results The combination of B7-H3 CAR-T cell therapy and IR has a greater killing effect on killing radiation-resistant CCSCs and bulk chordoma cells compared with CAR-T cell or IR monotherapy. Additionally, increased expression of B7-H3 antigens on CCSCs and bulk tumor cells is associated with enhanced CAR-T cell killing in vitro and in vivo xenograft mouse models. Upregulation of B7-H3 expression by IR increases CCSCs sensitivity to B7-H3 CAR-T cell-mediated killing.Conclusions Our preliminary data show that IR and B7-H3 CAR-T cell therapy is synergistically more effective than either IR or CAR-T cell monotherapy in killing chordoma cells in vitro and in a xenograft mouse model. These results provide preclinical evidence for further developing this combinatorial RT and B7-H3 CAR-T cell therapy model in chordoma